PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVA SD NEGERI 015 GURUN PANJANG KECAMATAN BUKIT KAPUR - Senti sirait sirait; Hendri Marhadi Marhadi; Gustimal witri witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study was conducted based on observations obtained data from the IVA- grade students learn science is still relatively lower than a predetermined KKM 75 school that the average value of the class with a percentage of 22,2% completeness. Therefore the researcher tried to apply the learning Model Pembelajaran Langsung (PBL) to improve science learning outcomes IVA SDN 015 gurun Panjang Kecamatan Bukit Kapur. This research is a from of action research (PTK) which consists of 2 cycles. Cycle I consists of 2 meetings and the second cycle consists of 2 meetings. The research instrument consisted of learning the syllabus, lesson plans, worksheets and activity sheets observation of teachers and students. The data analyzed in this study descriptive. The result of this study indicate that the learning outcomes of students has increased. At the first meeting of the teachers activities 81,25% and the second meeting of the first cycle to 87,5%. Of the second meeting of the first cycle to the first meetingf of the second cycle increased to 93,75% and from the first meeting of the second cycleto 96,87% at the second meeting of the second cycle. While the first meeting of the student activity first cycle is 46,87% and thesecond meeting of the first cycle of the second to meeting second cyclically increased to 56,25% fan on the second cycle increased to 78,12% at the second meeting of the second cycle increased to 93,75%. An increase  learningoutcomes of the averagebase score in the first cycle, from the first cycle increased to 41,18% in the second cycle is 56,86%. It can be concluded that if implemented Model Pembelajaran Langsung (PBL), it canboost science learning outcomes graders IVA SDN 015 Gurun Panjang Kecamatan Bukit kapur. Key Words: Model Pembelajaran Langsung (PBL), Learning Outcome IPA.